Partisipasi Masyarakat Dalam Pesta Demokrasi Tahun 2024 Kota Batam - Banjarnahor, Haposan; Husda, Anggun Permata; Ompusunggu, Hermaya; Rustam, Triana Ananda (Prosiding, 2024)
The results of the 2024 Election were determined by the Indonesian General Election Commission (KPU) on Wednesday, March 20, 2024. The determination of the results of the 2024 Election was stated in KPU Decree Number 360 of 2014 on Determination of the Results of the Presidential and Vice Presidential Elections, Members of the People's Representative Council, Regional Representative Council, Provincial People's Representative Council, and Regency/City People's Representative Councils nationally in the 2024 General Election. "Deciding, determining the KPU Decree on the Determination of the Results of the Presidential and Vice Presidential Elections, members of the People's Representative Council, Regional Representative Council, Provincial People's Representative Council, and Regency/City People's Representative Council nationally in the 2024 General Election. presidential and vice presidential candidate pair number 2, Prabowo Subianto-Gibran Rakabuming Raka, won with 96,214,691 votes. Prabowo dominates 36 of the 38 provinces in Indonesia. With the results of the 2024 Election, Prabowo is the President-Elect. Meanwhile, the presidential and vice presidential candidate pair number 1, Anies Baswedan-Muhaimin Iskandar, are in second place with 40,971,906 votes. This pair won in 2 of the 38 provinces in the country. Then, in third place is the presidential and vice presidential candidate pair number 3, Ganjar Pranowo-Mahfud MD who won 27,040,878 votes. Meanwhile, in the legislative election, the PDI Perjuangan was in first place with 25,387,279 votes from a total of 84 electoral districts (dapil). The Golkar Party was in second place with 23,208,654 votes. Meanwhile, the Gerindra Party was in third place with 20,071,708 votes. In the top four, the National Awakening Party (PKB) won 16,115,655 votes. In fifth place was the Nasdem Party with 14,660,516 votes.